Embedding Corporate Responsibility in the MBA Curriculum. - Marsden, Chris (Cranfield University School of Management, 2008)
The teaching of the role of Business in Society, Business and Sustainability, or Corporate (Social) Responsibility (C{S}R) as it is popularly known, in MBA programmes is still in its early stages. Where it happens it is most commonly found in an elective with, until recently, less than half the student cohort opting for it. There are a few compulsory modules, like the one the author teaches for the International Management School of the Ecole Nationale des Ponts et Chaussées (ENPC) in Paris and other venues. There are also a few specialist Masters programmes, for instance at Bath and Nottingham Universities.